Kropotkin and the anarchist intellectual tradition - Mac Laughlin, Jim (London : Pluto Press, 2016)
Rescues Kropotkin's philosophy of anarchism from the neglect that it has suffered in mainstream histories.
Cover; Title Page; Copyright; Dedication; Contents; 1 Anarchism Before Kropotkin; 2 Kropotkin: The Education of an Anarchist; 3 Kropotkin and the Legitimization of Anarchism; 4 'Scientific Anarchism' and Evolutionary Theory: Towards an Ontology of Anarchist Ethics and Altruism; 5 Kropotkin's Anarchism and the Nineteenth-Century Geographical Imagination: Towards an Anarchist Political Geography; Epilogue; Notes; Index.
Includes bibliographical references and index.
JSTOR
Keywords: Kropotkin, Petr Alekseevich, -- kni͡azʹ, -- 1842-1921.; Kropotkin, Petr Alekseevich, -- kni͡azʹ, -- 1842-1921; Kropotkin, Pëtr Alekseevič -- 1842-1921; Anarchism -- History; Anarchists -- Russia -- Biography; Anarchisme -- Histoire; Anarchistes -- Russie -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Political; POLITICAL SCIENCE -- Political Ideologies -- Communism & Socialism; Anarchism; Anarchists; Russia; Anarchismus; Politische Philosophie; Biographies; History; Biographies; Biographies